The Relationship of Self Regulated Learning with Academic Procrastination of Students of SMA Negeri 1 Tambun Selatan - Nurmawati Nurmawati; Bagas Prasetyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In the world of Education today, some problems often occur in high schools, namely academic procrastination, which is still carried out by students. Academic procrastination is the tendency of individuals to deliberately delay the start or completion of important and timely tasks on academic tasks. To reduce this impact, it is necessary to have self-control in learning that can support the achievement of learning goals by regulating and controlling a learning system known as self-regulated learning. This study aims to determine the relationship between self-regulated. I was learning with. Academic procrastination in SMAN 1 Tambun Selatan students. This study uses a correlational method with a quantitative approach. The sample in this study amounted to 110 students from class X and XI SMA Negeri 1 Tambun Selatan taken using a simple random sampling technique. The analysis technique used is the product-moment correlation technique with a significance level of 5%. Based on the analysis results, it is known that the F value is 0.798, and the significance value is 0.000 (P <0.05). The results showed a relationship between self-regulated learning and academic procrastination in students of SMA Negeri 1 Tambun Selatan.